Double Lung Transplantation for Idiopathic Pulmonary Fibrosis in a Patient with a History of Liver Transplantation and Prolonged Journey for Disease-Specific Antifibrotic Therapy. (13th August 2022) - Majewski, Sebastian; Królikowska, Maria; Costabel, Ulrich; Piotrowski, Wojciech J.; Ochman, Marek
Abstract : Idiopathic pulmonary fibrosis (IPF) is characterized by uncontrolled progressive lung fibrosis with a median survival of 3 to 5 years. Although currently available pharmacotherapy cannot cure the disease, antifibrotics including pirfenidone and nintedanib were shown to slow disease progression and improve survival in IPF. Nevertheless, there is a knowledge gap on the safety of antifibrotics in patients after liver transplantation receiving concomitant immunosuppressive therapy. This case report of a 68-year-old male patient with IPF illustrates how a complex medical history has led to diagnostic and therapeutic challenges considerably affecting clinical decisions and impacting the patient's journey. The increasing severity of lung function impairment due to the progressive natural history of IPF ultimately led to severe respiratory failure. Double lung transplantation (LTx) was performed as the only therapeutic option in end-stage disease with the potential to improve quality of life and survival. To the best of our knowledge, this is the first case report describing the feasibility and safety of antifibrotic therapy with pirfenidone for IPF in a 68-year-old patient with a history of liver transplantation receiving concomitant immunosuppressive therapy with tacrolimus who underwent successful double lung transplantation when alternative medical interventions had been exhausted.